TEKNIK PEMELIHARAAN LARVA KERAPU CANTANG (Epinephelus fuscoguttatus lanceolatus) - Imam Prayogo; Washil Isfanji (Faculty of Science and Technology University Ibrahimy, 2014)
Grouper (Epinephelus sp.) Is one type of sea fish that have high nutritional value and animal protein is good for consumption, besides groupers have bright market opportunities in the market both domestic and international market. The emergence of various problems with the grouper, the growers do hybridization (persilanagan). Hybridization was performed on a female tiger grouper and giant grouper males produce a new variety that is groupers cantang. This research was conducted with the aim to find out directly larval rearing techniques cantang grouper (Epinephelus sp.) And determine the factors that influence the process of maintenance. This study used survey method with the primary data collection is done through observation, interviews, documentation and direct participation in all activities of grouper hatchery cantang in Brackish Water Aquaculture Institute (BBAP) Situbondo. Secondary data was collected through literature. Maintenance activities of grouper larvae cantang in BBAP, include: the preparation of a tub, stocking and hatching eggs, larvae maintenance, feeding and harvesting.